Percutaneous Angioplasty and Stenting of Carotid Artery: Study of 18 Cases - Momenuzzaman, NAM; Begam, F; Khan, KN; Dey, A; Adhikary, DK; Ilius, ZM; Sohail, KM; Haque, F; Amin, MU; Rahman, R; et al. (Cardiovascular Journal, 2010)
Background: Carotid angioplasty & stenting is becoming an emerging therapeutic option for carotid revascularization. The use of cerebral protection system has expanded the area of application of the procedure worldwide. Purpose: To assess the feasibility, success rate, safety as well as in-hospital & early 30 days outcome in patients undergoing percutaneous carotid intervention. Methods: A retrospective, observational study where a total of 18 (Eighteen) consecutive patients who presented with symptomatic and > 70 % carotid artery stenosis & asymptomatic but > 90% stenosis underwent percutaneous carotid intervention. All of them had coronary artery disease; CABG was done in 3 patients & PCI in 9 patients. Three of them had previous stroke (Ischemic) & 7 had TIA. Results: Technical and angiographic success was achieved in all patients. Carotid artery obstruction diminishes from 85 ± 14 % to 10 ± 5 % (p< .001). Mean lesion length was 12 ± 3 mm and mean time of carotid occlusion during balloon inflation was 10 ± 2.5 sec. distal protection devices used in all patents. No major stroke or death occurred during procedure. One patient developed No-flow because of obstruction of distal protection device which was managed by thrombosuction. One patient developed TIA. All patients were discharged from hospital after an average of 3 days & all of them were prescribed dual antiplatalet therapy for 6 months. During follow-up one patient died secondary to acute myocardial infarction and one patient developed major stroke. Conclusion: Percutaneous angioplasty and stenting associated with distal protective devices appear feasible, effective and almost safe endovascular treatment modality for carotid artery stenosis. Key words: Carotid artery disease; Carotid angioplasty DOI: 10.3329/cardio.v2i2.6644 Cardiovasc. j. 2010; 2(2) : 218-222